0416 The Impact of Idiopathic Hypersomnia on Social and Romantic Relationships of Young Adults. (25th May 2022) - Davidson, Ryan; Blattner, Margot; Scammell, Thomas; Zhou, Eric
Abstract: Introduction: Idiopathic hypersomnia (IH) is a rare and debilitating neurologic disorder characterized by hypersomnolence, often beginning in adolescence. As IH has significant impacts on quality of life and may have greater social impact than narcolepsy, we studied how IH impacts social, romantic, and sexual relationships in young adults. Methods: Young adults (18-39 years; N=106) with a self-reported IH diagnosis were recruited through national patient organizations. Participants completed an online survey to evaluate social, romantic, and sexual relationships, and communication with medical providers. Results: Participants (mean=29.6 years; SD=5.2) were primarily female (90%), White/Caucasian (90%) and employed (80%). Almost all participants indicated that IH made social life or entering relationships more difficult (98% and 92%, respectively). Eighty-nine percent of participants indicated that IH had affected their sex life ("Too tired to engage in sexual activities or to feel aroused. …I want to sleep if I am in bed …"). IH symptoms impacted relationships in majority of participants (84%) and contributed to the breakup of a romantic relationship for almost 1 in 3 (32%). Rates of cohabitation and marriage were comparable to nationally representative samples. On the Multidimensional Scale of Perceived Social Support, participants reported receiving significantly more support from their significant others (mean=4.3; SD=1.8) compared to their family (mean=3.9; SD=1.6; p<.05) or friends (mean=4.0; SD=1.6; p<.05). There was no difference between the level of support received from family or friends (V = 2154; p =.77). Medical providers rarely asked about the social (34%) or sex lives (9%) of participants. In contrast, many participants wanted clinicians to ask about the impact of IH symptoms on social life (70%) and sex life (35%). Conclusion: IH substantially impacts social and romantic health in young adults. Similar to findings in narcolepsy, individuals with IH appear to prioritize romantic partnerships over other personal relationships. Many participants were interested in discussing their social and sexual relationships with their medical providers. However, only a small proportion of clinicians ask about these relationships. To provide effective treatment for the whole patient, clinicians should be prepared to evaluate and provide further support for the social health of young adults with IH. Support (If Any): Jazz Pharmaceuticals.